Norra Grunge - Karimi,Mohammad Mehdi (2025)
This thesis explores the potential of soundscape-based urban design to activate and regenerate Norra Grängesbergsgatan (NGBG), a post-industrial corridor in Malmö, Sweden. Rather than treating sound as a byproduct of urban life, the project positions it as a primary design medium one that can shape spatial experiences, encourage social interaction, and support cultural identity. The design introduces a layered system of auditory interventions to create a vibrant and inclusive urban atmosphere that responds to the rhythms of everyday life. Three key strategies structure the proposal: a Festival Street that hosts dynamic, large-scale events; a Cultural Corridor that supports creative expression and spontaneous performances; and Ambient Pocket Parks that offer spaces for reflection, play, and acoustic interaction. These spaces are designed to engage a broad spectrum of users—children, workers, creatives, and students—through interactive, multisensory, and participatory programming. Together, these interventions promote spatial diversity, temporal flexibility, and a playful exploration of sound in public space. Crucially, this thesis aligns with Malmö Stad’s strategic framework for the “Kulturljudzonen” (Cultural Sound Zone) in Sofielund and NGBG, which seeks to strengthen cultural infrastructure and activate underutilized urban areas through art and sound-based experimentation. By integrating municipal goals with speculative and place-based design, the project offers a model for how auditory experience can support long-term urban renewal, social cohesion, and creative placemaking in Malmö and beyond.
Keywords: Sustainable Urban Design; Soundscape; Urban renovation; activation